Leachate treatment by using aged refuse (AR) as a biofilter medium - Nik Daud, Nik Norsyahariati; Abu Mansor, Nursheela; Ahsan, Amimul; Idrus, Syazwani (Polish Journal of Environmental Studies, 2015)
The uncontrolled formation of leachate during a waste-disposal process has become a serious issue in landfill management. An innovative filtration process for treating leachate by using aged refuse as a medium in biofilter has been studied recently. The aim of this study is to treat leachate by using aged refuse varied by years (4, 8, and 11 years) as a biofilter medium. To achieve the target, a few objectives were listed: i) to construct the biofilter system in a laboratory scale, ii) to explore the use of aged refuse (AR) as a biofilter medium to treat leachate from the selected landfill in Malaysia, and iii) to assess the quality of leachate treated with different aged refuse regarding physical properties, chemical properties, and microbe activity. Results showed that the initial concentration of leachate parameters is: i) chemical oxygen demand (COD) was 981.47 mg/L, ii) biochemical oxygen demand (BOD) was 527.16 mg/L, and iii) ammonia-nitrogen (NH3-N) was 2,815.56 mg/L and iv) bacterial count is 3.3×106 CFUs. After treating with aged refuse, the quality of leachate is increased based on the concentration reduction of COD, BOD, and N H3-N in the range of 30% to 49%, 17% to 48%, and 68% to 92%, respectively.